1999
DOI: 10.1161/01.hyp.34.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Late Treatment With Ramipril Increases Survival in Old Spontaneously Hypertensive Rats

Abstract: Abstract-Spontaneously hypertensive rats (SHR) begin to die from cardiovascular complications at Ϸ15 months of age.We tested whether chronic ACE-inhibitor treatment would extend the lifespan of such old animals. We also studied cardiac hypertrophy and function, endothelial function and expression, and activity of NO synthase (eNOS). One hundred 15-month-old SHR were randomized into 3 groups, control (nϭ10), placebo-treated (nϭ45), and ramipriltreated with an antihypertensive dose of 1 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 in drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 25 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…Although in our study sham-operated SHR showed a significantly higher (6-to 7-fold) endothelial O 2 Ϫ production than the respective aortic endothelium of WKY, endotheliumdependent aortic relaxation was slightly greater in SHR than in aortas from sham-operated WKY. A reduced local bioavailability of NO caused by inactivation of NO through O 2 Ϫ despite a normal or even enhanced NO synthesis has been shown in endothelial dysfunction, for example, associated with hypertension, 18 hypercholesterolemia, 27 and high-salt diet. 28 One reason for elevated endothelial O 2 Ϫ formation may be a dysfunctional activity of eNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in our study sham-operated SHR showed a significantly higher (6-to 7-fold) endothelial O 2 Ϫ production than the respective aortic endothelium of WKY, endotheliumdependent aortic relaxation was slightly greater in SHR than in aortas from sham-operated WKY. A reduced local bioavailability of NO caused by inactivation of NO through O 2 Ϫ despite a normal or even enhanced NO synthesis has been shown in endothelial dysfunction, for example, associated with hypertension, 18 hypercholesterolemia, 27 and high-salt diet. 28 One reason for elevated endothelial O 2 Ϫ formation may be a dysfunctional activity of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic aorta was taken for evaluation of endothelial function 17 and for determination of NO and O 2 Ϫ production. 18 After evaluation of cardiac functions (contractility, dP/dt max , and aortic flow index, AFI) in the working heart, 18 wet weights of total heart and left and right ventricles were determined.…”
Section: Final Measurementsmentioning
confidence: 99%
“…Ren2 rats were randomly assigned to treatment groups at birth. After weaning at the age of 4 weeks, homozygous Ren2 rats were treated until the end of the observation period at 8 weeks of age with the ACE inhibitor ramipril (1 mg/kg/day) in drinking water (Ren2-ramipril) (Aventis Pharma Deutschland GmbH, Frankfurt am Main, Germany) (Linz et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Each isolated heart was perfused in the working-heart mode with a filling pressure of 15 mm Hg and an afterload pressure of 60 mm Hg, as described previously. 14 After the evaluation of cardiac performance, the heart was weighed, and the LV was sectioned transversely into 4 slices. Photographs were taken from each slice, and the tissues were then snap-frozen in liquid nitrogen and were stored at Ϫ80°C.…”
Section: Postinfarction Remodeling Modelmentioning
confidence: 99%